2017
DOI: 10.1139/cjm-2016-0773
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community structure and diversity within hypersaline Keke Salt Lake environments

Abstract: Keke Salt Lake is located in the Qaidamu Basin of China. It is a unique magnesium sulfate-subtype hypersaline lake that exhibits a halite domain ecosystem, yet its microbial diversity has remained unstudied. Here, the microbial community structure and diversity was investigated via high-throughput sequencing of the V3-V5 regions of 16S rRNA genes. A high diversity of operational taxonomic units was detected for Bacteria and Archaea (734 and 747, respectively), comprising 21 phyla, 43 classes, and 201 genera of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 53 publications
3
54
0
Order By: Relevance
“…Besides, several studies have focused on the biotechnological potential of its enzymes [7][8][9][10][11][12][13][14][15]. On the other hand, several culture-independent studies have also shown the presence of members of the genus Natronomonas in different environments from widely separated sites, such as hypersaline and alkaline lakes, solar salterns, saline-alkaline soils, and sediments or oil fields [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], supporting the widespread distribution of species of this genus.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, several studies have focused on the biotechnological potential of its enzymes [7][8][9][10][11][12][13][14][15]. On the other hand, several culture-independent studies have also shown the presence of members of the genus Natronomonas in different environments from widely separated sites, such as hypersaline and alkaline lakes, solar salterns, saline-alkaline soils, and sediments or oil fields [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], supporting the widespread distribution of species of this genus.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its richness in natural resources, studies of the microbial communities in the Qaidam Basin have mostly focused on salt lakes and gas fields. These studies focused exclusively on microbial communities and diversity in the salt lakes by isolating halophilic bacteria and studying microbial activity related to the formation of water and gas (Chen, Shuai, Osadetz, Hamblin, & Grasby, ; Duan et al, ; Han et al, ; Jiang, Xue, & Ma, ; Shen, ; Wang et al, ; Zhao et al, ). Soil microbes play an important role in maintaining soil quality and influencing nutrient availability.…”
Section: Introductionmentioning
confidence: 99%
“…15% in Punta Cormorant (PC6), 6% in the medium‐salinity pond SS19 from a marine saltern, 0.25% in the Salar Grande collection or between 2.8% and 0.18% in the Lake Mayghan samples (Ghai et al ., ; Crits‐Christoph et al ., ; Naghoni et al ., ). Remarkably, the bacterial community of Keke Salt Lake (China), rich in magnesium and sulfate, was also dominated by Firmicutes that accounted for 74%–81% of the 16S rRNA gene sequences, from which 51%–58% belonged to Bacillus species (Han et al, ). To the best of our knowledge, none of the saline metagenomes analysed so far presented the dominance of Pontibacillus sp.…”
Section: Resultsmentioning
confidence: 99%
“…Using culture‐dependent and molecular approaches, several athalassohaline aquatic systems have been described; e.g. inland haloalkaline lakes (Sorokin et al ., ; Vavourakis et al ., ); ephemeral water reservoirs such as the Salton Sea, California, USA (Hawley et al ., ); two hypersaline meromictic lakes in the Transylvanian Basin, Romania (Andrei et al ., ); the sulfated‐halophilic Tirez inland lake in Central Spain (Prieto‐Ballesteros et al ., ; Montoya et al ., ), the magnesium sulfate‐rich Keke Salt Lake in China (Han et al ., ), and the lithium and magnesium‐rich salt lake Salar de Uyuni (Haferburg et al ., ; Rubin et al ., ; Ramos‐Barbero et al, ,b). Non‐aquatic saline formations have also been subjected to microbial composition analysis, such as the Great Salt Plains of Oklahoma, USA (Crisler et al ., ); several halite‐rich deposits of the Atacama desert in Chile (halite, evaporite domes, microbial mats and crusts; Crits‐Christoph et al ., ; Rasuk et al ., ); salt‐crusts from evaporation ponds in Eilat, Israel (Oren et al ., ), and saline soils (Vera‐Gargallo and Ventosa, ).…”
Section: Introductionmentioning
confidence: 99%